The Effectiveness of Constructivism-based Arabic Textbook in Higher Education - Nasution, Sahkholid; Walad, Akmal (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This study aims (1) to describe the specifications of Constructivism-based-based Arabic Textbook, (2) to describe the process of Arabic learning using Constructivism-based Arabic Textbook, and (3) to describe the effectiveness of using Constructivism-based Arabic Textbook for mahÃ¢rah kitÃ¢bah (writing skill). This is a quasi-experimental study using data obtained through Questionnaires and Tests. The experiment was applied to students of the Arabic Language Education study program, Faculty of Tarbiyah and Teacher Training, at the University Islam Negeri Sumatera Utara, Medan, in the odd Semester of 2021-2022 academic year. Thirty-two participants were chosen as a sample of a total population of 97 people Questionnaires and tests were employed as the instruments to collect the data, which were further analyzed using the SPSS 16.0 program. The findings can be seen as follows. (1). The specification of Constructivism-based Arabic textbook can be expressed in a sentence, namely: al-QirÃ¢â€™atu wa KitÃ¢batuhs wa al-TahlÃ®lu maâ€™a KitÃ¢batin JadÃ®dah. It is called â€œal-QirÃ¢â€™ahâ€ because each chapter begins with the jumlah wazhifiy. It is called â€œKitÃ¢batuhÃ¢â€ because students are asked to rewrite jumlah wazhifiy they read. It is called â€œal-TahilÃ®lâ€ because students are required to analyze jumlah wazhifiy. It is called â€œKitÃ¢bah JadÃ®dahâ€ because students are instructed to construct new wazhifiy related to tarkÃ®b. (2). The learning is known as "Nyari Zoom Analis Dewa", and it stands for "Penyajian Materi dengan Zoom, Latihan Menulis dengan WAâ€ (Literally translated as the presentation conducted through Zoom, the writing practice conducted through WhatsApp) (3). The Constructivism-based Arabic textbook for mahÃ¢rah kitÃ¢bah is considered adequate based on the validatorsâ€™ assessment and experiment results. The results showed that Ho was rejected and Ha was accepted. There was an average difference between the Pretest and Posttest. The Pretest result was lower than the Posttest. Therefore, a Constructivism-based Arabic textbook is effective in increasing the mahÃ¢rah kitÃ¢bah.